Enhancing the use of mosquitoes in disease surveillance through spatially explicit entomological risk indices and the validation of Xenosurveillance - Fauver, Joseph R., author; Gregory, Ebel D., advisor; Foy, Brian D., committee member; Moore, Chester G., committee member; Peel, Jennifer L., committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.
Keywords: disease surveillance; Xenosurveillance; insect-specific virus; West Nile virus; Anopheles